Health promoting activities and corresponding mechanism of (–)-epicatechin-3-gallate - Zhiliang Li; Changchun Feng; Hongjin Dong; Weibin Jin; Wenying Zhang; Jianfeng Zhan; Shuzhen Wang (Food Science and Human Wellness)
ABSTRACT: (–)-Epicatechin-3-gallate (ECG), a bioactive polyphenolic compound, has contributed a lot to the health benefits of green tea. Great attention has been focused on (–)-epigallocatechin-3-gallate (EGCG), but limited research has been performed towards ECG. Like EGCG, ECG also possesses various pharmacological and physiological properties, such as mediation of antioxidant activities, anti-inflammation response, regulation of cell proliferation and apoptosis, as well as anticancer properties during angiogenesis, invasion and metastasis stages. Nontoxic ECG has various molecular targets within the cells, including CYP enzymes, phase II detoxification and antioxidant enzymes, as well as pro-inflammatory mediators. The antineoplastic mechanism contains inhibition of phase 1 CYP enzymes, induction of phase II detoxification and antioxidant enzymes, high anti-inflammatory efficacy, arrest of cell cycle progression, regulation of apoptosis, as well as mediation of metastasis processes. In particular, the gallate moiety of ECG is critical for mediating inhibitory effects towards cancer cells. Besides regulation of intracellular signaling pathways, ECG also inhibits RNase A and matrix metalloproteinase enzymatic activity via chelating metals (copper and zinc) in cancer cells. This review has summarized recent studies on pharmacological properties of ECG, and discussed corresponding mechanism on modulation of cellular signaling events by ECG, hoping to broaden its multiple usage.